KEMAMPUAN MENULIS SURAT PRIBADI PADA SISWA KELAS VII SMP NEGERI 1 NANGGUNG TAHUN PELAJARAN 2023/2024 - Supriyatna, Encim; Utami, Dian Marliyanti; Handayani, Fitriyah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Writing skills are very important for students, one of which is writing personal letters. However, in today's digital era, personal letters are rarely used, even some students do not know what a personal letter is. This study aims to determine the ability to write personal letters to grade vii students at SMP Negeri 1 Nanggung. The subjects of this study were students of grade vii at SMP Negeri 1 Nanggung. This research uses a qualitative descriptive method, which means that the research describes the level of students' ability to write personal letters. The study used a sample of 32 people from several different classes. The data collection technique is a performance test, by means of which each student writes a personal letter. This research was conducted on April 24, 2024. With the results that the ability to write personal letters at SMPN 1 Nanggung no one scored less. So it can be concluded that the ability to write personal letters at SMPN 1 Nanggung is good even though they no longer write personal letters in communication.